Somatic mutation and clonal expansions in human tissues - Inigo Martincorena (Genome Medicine, 2019)
Editorial summary Recent sequencing studies on healthy skin and esophagus have found that, as we age, these tissues become colonized by mutant clones of cells carrying driver mutations in traditional cancer genes. This comment summarizes these findings and discusses their possible implications for our understanding of cancer, ageing, and other diseases.